2004
DOI: 10.1111/j.1439-0396.2003.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Brown seaweed‐ (TascoTM) treated conserved forage enhances antioxidant status and immune function in heat‐stressed wether lambs

Abstract: Twenty-seven wether lambs were utilized to evaluate select innate immunity and oxidative stress in response to diet and heat stress. Dietary treatments were: (i) control (tall fescue) hay = no Tasco (tradename for the extract of the brown seaweed, Ascophyllum nodosum, Acadian Sealants Ltd, Nova Scotia, Canada); (ii) pre-harvest Tasco-Forage-treated hay and (iii) control hay + post-harvest Tasco-EX. Tasco-Forage and Tasco-EX are two forms of the Tasco extract that are either applied to foliage or used for direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 19 publications
4
49
1
Order By: Relevance
“…2) in group E, is in agreement with the findings of Archer et al (2007), Chiu et al (2008) and Saker et al (2004) on the priority effects of brown seaweed on the enhancement of nonspecific immunity parameters (antioxidants, cytokinins) and 50% decrease in the specific immunity response to ovoalbumin. To achieve the required effect of brown seaweed alginates on the enhancement of nonspecific immunity and weakening of specific immunity doses higher than 2 g of seaweed per kg of complete feed ration were mostly used in the above-mentioned studies (Turner et al 2002, Saker et al 2004, Archer et al 2007, which markedly exceeds the intake of seaweeds in group E (Table 1). The results obtained significantly accentuate the risk of diet enrichment with seaweed in sheep arising already at an amount of 71 mg per head day -1 at targeted specific immunization (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2) in group E, is in agreement with the findings of Archer et al (2007), Chiu et al (2008) and Saker et al (2004) on the priority effects of brown seaweed on the enhancement of nonspecific immunity parameters (antioxidants, cytokinins) and 50% decrease in the specific immunity response to ovoalbumin. To achieve the required effect of brown seaweed alginates on the enhancement of nonspecific immunity and weakening of specific immunity doses higher than 2 g of seaweed per kg of complete feed ration were mostly used in the above-mentioned studies (Turner et al 2002, Saker et al 2004, Archer et al 2007, which markedly exceeds the intake of seaweeds in group E (Table 1). The results obtained significantly accentuate the risk of diet enrichment with seaweed in sheep arising already at an amount of 71 mg per head day -1 at targeted specific immunization (Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, the majority of the findings up to now have demonstrated the enhancement only of nonspecific immunity. The short-time enhancement of the oxidative burst of monocytes and increased activity of glutathione peroxidase in lambs after the application of brown seaweeds were reported by Saker et al (2004). Cheng et al (2005) and Chiu et al (2008) found in crustaceans and fish that the application of 1-2 g sodium alginate per kg diet increased the complement and lysozyme activity, respiratory burst of monocytes and phagocytic activity.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, they found a positive effect on the activity of serum lysozyme. Positive effects on the immune system and resistance to stress in sheep have been described by Saker (2004).…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation processes of all living organisms are very intrinsic in the energy management, and are, therefore, should be kept under strict control by several cellular mechanisms [7]. Several types of extracts obtained from seaweeds have received special attention due to their potent pharmaceutical activities, including anticancer, immune-stimulant and antioxidant activities [8]. Seaweeds contain high amounts of polyphenols.…”
Section: Introductionmentioning
confidence: 99%